Comparative study regarding agility between u18 and u16 handball players from university sports club of Suceava - Andreea - Gabriela Boca; Vasile Costel Boca (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
The purpose of this study was to evaluate the agility and the running speed of male handball players in Category Junior Team of University Sports Club of Suceava and then make the comparasion between the results obtained by players from U16 and those from U18. The sample of participants consisted of 32 male junior handball players, divided into two groups: 18 handball players U16 (age 15.27±0.57 years), and 14 handball players U18 (age 17.14±0.77). To test agility we used Illinois Test that involves various turns and movements. At the end of the research, it was shown that there were no significant differences calculated between under 18 and under 16 handball junior players in agility (p =.38). Even if there was a difference between arithmetic means (17.49±1.52; 17.08±0.97), that was not statistically significant.